Surgical Success in Chronic Pancreatitis: Sequential Endoscopic Retrograde Cholangiopancreatography and Surgical Longitudinal Pancreatojejunostomy (Puestow Procedure) - Ford, Kathryn; Paul, Anu; Harrison, Phillip; Davenport, Mark (European Journal of Pediatric Surgery, 2016)
Introduction Chronic pancreatitis (CP) can be a cause of recurrent, severe, disabling abdominal pain in children. Surgery has been suggested as a useful therapy, although experience is limited and the results unpredictable. We reviewed our experience of a two-stage protocol—preliminary endoscopic retrograde cholangiopancreatography (ERCP) and duct stenting, and if symptoms resolved, definitive surgical decompression by longitudinal pancreatojejunostomy (LPJ) (Puestow operation).Patients and Methods This is a single-center, retrospective review of children with established CP who underwent an LPJ between February 2002 and September 2012. A questionnaire was completed (incorporating visual analog scale pain and lifestyle scores) to assess functional outcome. Data are expressed as median (range).Results In this study, eight (M:F ratio of 4:4) children underwent an LPJ and one female child had a more limited pancreatojejunostomy anastomosis following preliminary ERCP and stent placement where possible. Diagnoses included hereditary pancreatitis (n = 3), idiopathic or structural pancreatitis (n = 5), and duct stricture following radiotherapy (n = 1). Median duct diameter presurgery was 5 (4–11) mm. Endoscopic placement of a Zimmon pancreatic stent was possible in six with relief of symptoms in all. Median age at definitive surgery was 11 (range, 7–17) years with a median postoperative stay of 9 (range, 7–12) days and a follow-up of 6 (range, 0.5–12) years. All children reported markedly reduced episodes of pain postprocedure. One developed diabetes mellitus, while three had exocrine deficiency (fecal elastase < 200 µg/g) requiring enzyme supplementation. The child with limited LPJ had symptomatic recurrence and required restenting and further surgery to widen the anastomosis to become pain free.Conclusion ERCP and stenting provide a therapeutic trial to assess possible benefit of a definitive duct drainage procedure. LPJ—the modified Puestow operation was safe and complication-free with good medium-term relief of symptoms. We were not able to identify a consistent etiology-associated outcome.
Keywords: chronic pancreatitis; Puestow procedure; hereditary pancreatitis; ERCP